Penggunaan Media Pembelajaran Sway pada Pembelajaran Membaca Permulaan di Sekolah Dasar - Fitri Yanty Muchtar; Nur Fitri Ramadhani; Miftahul Rahmi; Nurjanna Nurjanna; Wachdania R; Muhammad Ilham S (Journal on Education, 2023)
The use of image and SWAY media can improve students' reading skills in the Indonesian language at State Elementary School 32 Tumpumpua VI. This type of research uses the classroom action research method, which consists of two cycles. The research procedure includes planning, implementation, observation, and reflection. The research subjects are grade 1 students, a total of 28 students, 13 male and 15 female. The research results show an improvement in students' learning achievements in the skill of reading beginners in the second cycle, from a success rate of 57% completed with an average score of 70.86 in the first cycle to 100% completed with an average score of 83.82 in the second cycle. SWAY learning media can improve students' reading beginner skills in various ways, such as attractive visualization, enjoyable learning, flexible, interactive, and personalized. Therefore, the use of SWAY learning media needs to be applied and implemented in elementary school learning to improve students' learning achievements.